Hematopoietic Differentiation of Human Pluripotent Stem Cells - Cheng, Tao.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book features the most cutting-edge work from the world’s leading laboratories in this field and provides practical methods for differentiating pluripotent stem cells into hematopoietic lineages in the blood system. Pluripotent stem cells have attracted major interest from a fast-growing and multidisciplinary community of researchers who are developing new techniques for the derivation and differentiation of these cells into specific cell lineages. These direct differentiation methods hold great promise for the translational applications of these cells. This book is an essential reference work for researchers at all levels in the fields of hematology and stem cell biology, as well as clinical practitioners in regenerative medicine.
Generation of Hemangioblasts from Human Pluripotent Stem Cells -- Derivation of mature erythrocytes from human pluripotent stem cells by coculture with murine fetal stromal cells -- Derivation of megakaryocytes and platelets from human pluripotent stem cells -- Derivation of functionally mature eosinophils from human pluripotent stem cells.- Human Pluripotent Stem Cells As a Renewable Source of Natural Killer Cells -- Generation of T lineage cells from iPS cells and its application -- Reprogramming of Human Cord Blood CD34+ Cells into Induced MSCs -- CRISPR/Cas9-Mediated Genome Editing in Human Pluripotent Stem Cells -- Humanized mouse models with functional human lymphoid and hematopoietic systems through human hematopoietic stem cell and human fetal thymic tissue transplantation.
Keywords: Immunology; Stem cells; Laboratory medicine; Immunology; Stem Cells; Laboratory Medicine